A synthetic RNA-based biosensor for fructose-1, 6-bisphosphate that reports glycolytic flux. Issue 11 (18th November 2021) - Ortega, Alvaro Darío; Takhaveev, Vakil; Vedelaar, Silke Roelie; Long, Yi; Mestre-Farràs, Neus; Incarnato, Danny; Ersoy, Franziska; Olsen, Lars Folke; Mayer, Günter; Heinemann, Matthias
Summary: RNA-based sensors for intracellular metabolites are a promising solution to the emerging issue of metabolic heterogeneity. However, their development, i.e., the conversion of an aptamer into an in vivo -functional intracellular metabolite sensor, still harbors challenges. Here, we accomplished this for the glycolytic flux-signaling metabolite, fructose-1, 6-bisphosphate (FBP). Starting from in vitro selection of an aptamer, we constructed device libraries with a hammerhead ribozyme as actuator. Using high-throughput screening in yeast with fluorescence-activated cell sorting (FACS), next-generation sequencing, and genetic-environmental perturbations to modulate the intracellular FBP levels, we identified a sensor that generates ratiometric fluorescent readout. An abrogated response in sensor mutants and occurrence of two sensor conformations—revealed by RNA structural probing—indicated in vivo riboswitching activity. Microscopy showed that the sensor can differentiate cells with different glycolytic fluxes within yeast populations, opening research avenues into metabolic heterogeneity. We demonstrate the possibility to generate RNA-based sensors for intracellular metabolites for which no natural metabolite-binding RNA element exits. Graphical abstract: Highlights: RNA sensor for intracellular metabolite (FBP) developed from a synthetic aptamer Aptamer obtained that binds FBP in its intracellular concentration range In vivo screening of sensor libraries with the aptamer fused to a hammerhead ribozyme Developed sensor reports FBP in single cells and revealed metabolic heterogeneity Abstract : Current RNA sensors for intracellular metabolites employ aptamers from natural riboswitches. Ortega et al. developed a genetically encoded RNA sensor for fructose-1, 6-bisphosphate to assess glycolytic flux in single cells. The study demonstrates the successful conversion of a synthetic aptamer for an endogenous metabolite into an RNA sensor.